Pemikiran Politik Islam Klasik dan Pertengahan: Tinjauan terhadap Konsep Hubungan Agama dan Negara - Sukron Kamil (Refleksi: Jurnal Kajian Agama dan Filsafat, 2005)
The thought and practice of Islamic politics are highly diverse, spanning various historical periods that have shaped the Islamic world. Therefore, it cannot be understood through a single perspective that may lead to biased judgments, as often done by the West. It is undeniable that throughout its history, Islam has given rise to a variety of political practices, ranging from authoritarian to democratic. This article aims to examine the treasury of classical and medieval Islamic political thought related to several issues such as the relationship between religion and state, the legitimacy of authoritarianism, forms of theocratic government, democracy, and aristocracy, as well as issues concerning the ideal society. Through this exposition, it is hoped that a more comprehensive understanding of Islamic political concepts developed during classical and medieval periods and their relevance to the present can be attained.